First species of Ophiotaenia (Cestoda: Proteocephalidea) from Madagascar: O. georgievi sp. n., a parasite of the endemic snake Leioheterodon geayi (Colubridae) - Chambrier, Alain de; Ammann, Morgane; Scholz, Tomáš (Folia parasitologica, 2010)
Ophiotaenia georgievi sp. n. (Proteocephalidea: Proteocephalinae) is described from the intestine of endemic colubrid snake Leioheterodon geayi Mocquard (Colubridae) from Antananarivo in Madagascar. The new species is the first species of Ophiotaenia La Rue, 1911 reported from Madagascar. It differs from all Ophiotaenia species parasitic in African snakes in the possession of a three-layered embryophore of eggs (other African species have two-layered embryophore). Furthermore, O. georgievi can be distinguished by the number of testes (92-140), width of the scolex (225-235 jm), total body length (57 mm), cirrus-sac length/proglottis width ratio (19-32%), and number of lateral uterine diverticula (23-28 on each side). Ophiotaenia georgievi represents the second proteocephalidean cestode reported from Madagascar, the first one being Deblocktaenia ventosaloculata (Deblock, Rosé et Broussart, 1962), a parasite from Ithycyphus miniatus. A list of Ophiotaenia species parasitic in venomous and non-venomous snakes is provided and possible existence of other new congeneric species in snakes from Madagascar is discussed.
Keywords: Cestoda; Financing, Organized; Cestode Infections; Colubridae; Animals; Madagascar; financování organizované; cestodózy; parazitární nemoci u zvířat; zvířata; Madagaskar; Parasitic Diseases, Animal